CURVE FITTING IN MATLAB – TRIGONOMETRIC POLYNOMIAL (Perner's Contacts, 2011)
The article deals with derived, algorithm design and description of the trigonometric polynomial. There are described and explained the basic computational procedures regarding this issue, first is always a theoretical analysis, followed by solved examples and extracts functions in Matlab with explanatory commentary.
Keywords: Trigonometric polynomial; algorithms; approximation; Matlab